The Influence of Work-Life Balance and Emotional Intelligence on Employee Engagement through Job Satisfaction as an Intervening Variable in the Textile Industry - Breliana Rasita; Eneng Wiliana (LP2M IAIN Palopo, 2026)
This research explores the role of work-life balance and emotional intelligence in shaping employee engagement, while also considering the mediating function of job satisfaction. Adopting a quantitative approach, data were collected through questionnaires distributed to 147 production employees in an Indonesian textile company. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the support of SmartPLS 4 software. The findings reveal that both work-life balance and emotional intelligence contribute significantly to enhancing job satisfaction and employee engagement. Furthermore, job satisfaction is found to partially mediate the relationship between these variables, indicating that improvements in work-life balance and emotional intelligence can indirectly strengthen employee engagement through increased satisfaction. These results underline the importance of organizational efforts to promote a healthier balance between professional and personal life, alongside the development of employees’ emotional capabilities. Such initiatives can foster more positive work attitudes and higher engagement levels. Future research is encouraged to incorporate additional organizational and psychological variables, as well as to examine these relationships across diverse industry settings.